Pengembangan Training of Trainer (TOT) Kesehatan Reproduksi dan Psikologi pada Santriwati sebagai Upaya Pengurangan Kasus Pernikahan Dini di Sumenep Madura - Kurniawati, Eighty Mardiyan; Nawangsari, Nur Ainy Fardana; Rahmawati, Nur Anisah; Safitri, Cahyani Tiara; Kurniawan, Agde Muzaky; Rodhiyana, Rosda; Mustofa, Vina Firmanty (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Early marriage has both short-term and long-term consequences. Reproductive A variety of problems related to her health and mental or psychological health can occur. Young people must be given full understanding. This non-profit effort aims to promote Youth Trainer Training (TOT) activities to increase young people's understanding of the youth psychology associated with reproductive health and early marriage, and to disseminate the information received. This activity is an attempt to reduce early marriage in Sumenep Madura. Activities carried out include reproductive health materials provided by obstetricians and gynecologists, adolescent psychology materials provided by psychologists, Training of Trainers (TOT) aimed at facilitating trainers and peer counselors. This includes improving communication skills and critical thinking in Train all schoolgirls and use workshops/training to create digital works in the form of health promotion media posters and/or educational videos using works based on local wisdom. The activities carried out can enhance young people's knowledge of reproductive health, psychology, communication skills and media production. Subsequent activities, including parents, require regular training to reduce early marriage.